China's artificial islands in the south China sea: geopolitics versus rule of law - Swaran Singh; Lilian Yamamoto (Revista de Direito Econômico e Socioambiental)
China’s construction of artificial islands during last few years has raised concerns about militarisation of the South China Sea threatening stability and security for littoral countries. China claims over 80 per cent of the South China Sea and it is building landing and garrison facilities over geographical features classified as rocks and coral reefs. China's claims are grounded on their supposed discovery and occupation of these features since antiquity. Other claimants, like the Philippines, Vietnam, Malaysia, Taiwan, Brunei and Indonesia, have their own historical narratives and cite articles of the UN Convention on the Law of the Sea (UNCLOS) to justify their sovereignty over part of this disputed maritime region. This multilateral nature of dispute makes it extremely complicated and China's increasingly assertive policies have further compounded it. Accordingly, several nations, including United States, have raised alarm regarding freedom of navigation across the South China Sea. It in this backdrop of rising tensions that this article examines these multiple narratives and what UNCLOS and the Permanent Court of Arbitration say in clarifying the legality of maritime rights to crystal gaze likely future trajectories. However, this study also recognizes that while UNCLOS remains at the core of maritime dispute settlement, it is the evolving geopolitics of Asia that will go a long way in guiding both the interpretation of UNCLOS as also state responses in terms of their proposals for joint development or unilateral strategies.